Simulation analysis on vaporizer/mixer performance of the high-pressure SCR system in a marine diesel - Zhu, Yuanqing; Li, Tinghui; Xia, Chong; Feng, Yongming; Zhou, Song (Chemical engineering and processing, 2020)
[Display omitted] •Evaluated flow field and concentration field of vaporizer/mixers installed with five structural flow-guiding plates.•Analyzed pressure change law of the front and the back of flow-guiding plate.•The vaporizer/mixer installed with irregular trapezoidal plates is more adaptive to the HP-SCR system. As an important part of high-pressure SCR system in a marine diesel, vaporizer/mixer is a vital place to improve the spray atomization of urea solution, the formation of reduction agent and the effective mixing of multiple components well. In this paper, vaporizer/mixer of high-pressure SCR (HP-SCR) system in a marine diesel engine was selected as the research subject, then I establish a three-dimensional model of the mixer by CFD and simulate the chemical reaction fluid dynamic by Fluent, and then its major design properties of pressure loss, flow velocity and species concentration uniformity, NH3/NOx deviation as well as sensitiveness of diesel load were studied. According to characteristics of vaporizer/mixer of high-pressure SCR system, working performances of vaporizer/mixer installed without and with flow-guiding plates were compared and analyzed, and mixing effects of five flow-guiding plates were also evaluated in the paper. It is found that both the vaporizer/mixers which are installed with the centralized curved plates and irregular trapezoidal plates can meet the needs of design requirements of HP-SCR system, and the vaporizer/mixer installed with the irregular trapezoidal plates is superior to other structural flow-guiding plates. In addition, compared with vaporizer/mixer without flow-guiding plate, the maximum pressure loss of the vaporizer/mixer installed with irregular trapezoidal plates is only increased by 126 Pa, but its NH3 concentration uniformity in the outlet is increased by 8.1 %, and the sensitiveness efficiency of diesel load is decreased to 0.1 %, which adapts to the various working conditions of high-pressure SCR system in the low-speed marine diesel.